Application of Cellulase Enzyme in Feed on the Growth of Siamese Catfish (Pangasius hypophthalamus) - Anjasmara, L. Dede Arta Satya; Amin, Muhamad; Mukti, Akhmad Taufiq; Mahasari, Gunanti; Agniny, Siswi Fililmi; Ali, Muhamad (Pascasarjana, Mataram University, 2025)
Siamese catfish (Pangasius hypophthalamus) is one of the most economically importantfreshwater commodities in Indonesian aquaculture. A major challenge during the growth-out phase, is the limited ability to digest plant-based diets due to high cellulose and crude fiber content, which reduce feed digestibility. Supplementation of cellulase in feed has been proposed as a strategy to improve nutrient utilization. Therefore the present study investigated the effect of dietary celulase supplementation on feed digestibility and growth performance in Seamese catfish. Juvenile catfish with an average initial length of 6cm were reared for 30 days in floating net in a cement pond. A complete reandomized design was employed with four treatments, two control, and four replciates. Treatments included cellulase derived from mivrobes sources T1 = Plant feed + WT, T2 = Plant feed + (WT + SKIK), T3 = Plant feed + Mutant, T4 = Plant feed + (mutant + SKIK). The control consisted of C1 = Commercial feed and C2 = Plant-based feed without enzyme supplementation. The results showed that C1 showed the best results for the growth of fish. However, T2, T3 and T4 showed the best results when compared to C2 and T1 which used 100% vegetable protein feed. Therefore, it can be concluded that the addition of cellulase enzymes to the feed has an effect on increasing the growth of Siamese catfish.